2017
DOI: 10.1590/1809-4430-eng.agric.v37n4p750-759/2017
|View full text |Cite
|
Sign up to set email alerts
|

Data Mining Techniques for Separation of Summer Crop Based on Satellite Images

Abstract: Due to the difficulty in discriminating soybean and corn in mappings obtained by the time series of satellite images, this study aimed to apply the data mining techniques to separate soybean and corn. Pure pixels selection from Landsat-8 were extracted and used to build a standard spectro-temporal EVI profile for both crops. These profiles were obtained with the Timesat software and, further incorporated in the Weka software. Five out of eleven variables of the standard spectro-temporal EVI profile for each cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Thus, agro-climatic zoning, especially for the second summer crop, recommends early planting in order to avoid risky periods. These results are similar to those obtained by Johann et al (2016) and Becker, Johann, Richetti and Silva (2017). However, they retrieved dates from soybean areas in a municipality level, while this study shows by pixel scale.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, agro-climatic zoning, especially for the second summer crop, recommends early planting in order to avoid risky periods. These results are similar to those obtained by Johann et al (2016) and Becker, Johann, Richetti and Silva (2017). However, they retrieved dates from soybean areas in a municipality level, while this study shows by pixel scale.…”
Section: Introductionsupporting
confidence: 90%
“…Corn harvest varied across the state, like SD and DMVD. Becker et al (2017) also observed similar pattern. This is due to the possibility of maintaining corn in the field after it is ready for harvest, which does not apply to other agricultural crops as it could cause grain loss.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Agrometeorological variables, in the most critical phenological phases of the soybean cycle, were analyzed, that is, in the intervals close to the maximum vegetative development date (MVDD), defined by Becker et al (2017) as the crop's reproductive stages (flowering, pod formation and filling). For the two harvest years, the MVDD was obtained from Becker et al (2020).…”
Section: Determination Of the Study Area And Data Acquisitionmentioning
confidence: 99%
“…Thus, new Deep Learning architecture should be tested in order to facilitate and create a streamline for this process in agricultural mapping. One of the options which is gaining recognition in remote sensing is the use of the KDD (Knowledge Discovery in Databases) process that aims to transform a large amount of data into useful information, as reported in several studies (Becker et al 2017;Han and Kamber 2006;Hansen et al 2000;Johann et al 2013;Zhou et al 2013).…”
Section: Introductionmentioning
confidence: 99%